2017
DOI: 10.1590/2179-8087.029315
|View full text |Cite
|
Sign up to set email alerts
|

Amenizante Orgânico e Eucalyptus grandis para Fitoestabilização de Solo Contaminado com Cobre

Abstract: RESUMOEste trabalho avaliou a utilização de turfa como amenizante e Eucalyptus grandis como técnica de fitoestabilização para remediar solo contaminado com cobre. O trabalho foi conduzido sob delineamento inteiramente casualizado em arranjo fatorial (2 × 6), sendo sem e com adição de turfa (200 mL L -1 de solo) e seis doses de cobre adicionadas ao solo (0 mg kg -1 , 60 mg kg -1 , 120 mg kg -1 , 180 mg kg -1 , 240 mg kg -1 , 300 mg kg -1 de solo), com seis repetições. Avaliaram-se a altura das mudas, o diâmetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In indirect phytoremediation, vegetables extract contaminants from groundwater, performing external degradation, reducing the source of contamination, and releasing compounds that favor microbial activity in the rhizosphere (Fellet and Marchiol 2011;Ting et al 2018;Yan et al 2020). The indirect mechanisms are i) phytostabilizationthe ability of plants to reduce the mobility or migration of contaminants present in the soilthis mechanism depends on the incorporation of the compound in soil humus or lignin; and ii) phytostimulationplants perform microbial degradation of contaminants (De Marco et al 2017;Melo et al 2010;Santos et al 2007). However, the choice of mechanisms can influence some variables, such as pH, humidity, and nutrients, which can cause disadvantages and increase the recovery time (Yan et al 2020).…”
Section: Evaluation Of Phytoremediation Mechanisms For the Treatment ...mentioning
confidence: 99%
“…In indirect phytoremediation, vegetables extract contaminants from groundwater, performing external degradation, reducing the source of contamination, and releasing compounds that favor microbial activity in the rhizosphere (Fellet and Marchiol 2011;Ting et al 2018;Yan et al 2020). The indirect mechanisms are i) phytostabilizationthe ability of plants to reduce the mobility or migration of contaminants present in the soilthis mechanism depends on the incorporation of the compound in soil humus or lignin; and ii) phytostimulationplants perform microbial degradation of contaminants (De Marco et al 2017;Melo et al 2010;Santos et al 2007). However, the choice of mechanisms can influence some variables, such as pH, humidity, and nutrients, which can cause disadvantages and increase the recovery time (Yan et al 2020).…”
Section: Evaluation Of Phytoremediation Mechanisms For the Treatment ...mentioning
confidence: 99%
“…Regarding plant species, the Eucalyptus genus encompasses more than 600 species, presents good adaptation to the Brazilian climatic conditions, with relatively fast growth and development, and large biomass production (Magalhães et al, 2011). However, studies by De Marco et al (2017) have showed that the Eucalyptus grandis seedlings have high capacity to accumulate Cu in their root system, which would enable its use for phytostabilization, but there are still few studies including the use of different eucalyptus species.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…In plants, high copper levels induce decreased growth, chlorosis and foliar necrosis (ANJUM et al, 2015). Metal toxicity is evident in the reduced root length, biomass and production of photosynthetic pigments, as well as a decline in the absorption of essential nutrients by the plants (DE MARCO et al, 2017;XU et al, 2017). According to CAETANO et al, (2016), 28mg kg -1 (USEPA method) are damaging to the development of plants and other soil organisms.…”
Section: Introductionmentioning
confidence: 99%